The employee's perception towards the adaptation of the new management inventory system in Xyratex (Malaysia) Sdn.Bhd. Senawang, 2007 / Nurashikin Abd Gani - Abd Gani, Nurashikin (Faculty of Business and Management, 2007)
This research was conducted for the purposed to know the employees' perception toward the adaptation of the inventory systems in Xyratex (Malaysia) Sdn.Bhd. Senawang. The main objective of this research was to determine the level of availability, operational performance, reliability and employees' perception of the new inventory system. Moreover, this study wants to determine the factors that affect employee perception towards the adaptation of the new management inventory system. It is also want to determine the relationship between employee perception and the adaptation of the new inventory system. Beside that this study also wants to determine the relationship between the basic service capability which is availability, operational performance and reliability of the new inventory system toward the employees' perception. In this study the researcher using Basic Service Capability model as the theoretical framework. The objective and also the questionnaire designed based on this framework. The respondent of this study was Xyratex Staff especially the warehouse staff. 65 questionnaires had been distributed to them. The researcher had used simple random sampling as the sampling technique. In analyzing the data the researcher used frequency table and also correlation. The conclusion of this study was the outcome from the survey analysis and findings. Through the research, it shows their perception level toward the new inventory management system is moderate.